KANDUNGAN SERAT, LEMAK, SIFAT FISIK, DAN TINGKAT PENERIMAAN ES KRIM DENGAN PENAMBAHAN BERBAGAI JENIS BEKATUL BERAS DAN KETAN - Puspitarini, Riza; Rahayuni, Arintina (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Fiber intake provides many health benefits including reduced risk for coronary heart disease, stroke, hypertension, diabetes, obesity and certain gastrointestinal disease. One of the foods that have high fiber content is rice bran. The addition of rice bran in ice cream to enrich the fiber content of ice cream, so that the ice cream is produced has more complete nutritional value. White rice, red rice, white glutinous rice, and black glutinous rice are well known by Indonesian people. Therefore, it is necessary to study about fiber and fat content of ice cream with the addition of white, red, white glutinous, and black glutinous rice bran. Objective: Analyze the difference of fiber content, fat content, physical properties (overrun and melting rate), and level of acceptance by the addition different types of rice and glutinous rice bran in ice cream. Methods: Experimental study completely randomized design with single factor. Rice bran varieties used were white, red, white glutinous, and black glutinous rice bran with addition of 10% rice bran. The analyzes are crude fiber content, fat content, physical properties, and level of acceptance of ice cream with the addition of rice and glutinous rice bran varieties. Data described the physical properties of ice cream by calculating the average overrun and melting rate. Statistical analysis of the fiber content using one way ANOVA, while the fat content using Kruskal-wallis. The level of acceptance analyzed by Friedman test followed Wilcoxon test. Results: The addition of different types of rice and glutinous rice bran statistically no effect on fiber and fat content of ice cream. The highest overrun is in the ice cream without the addition of rice bran. The lastest melting rate is in the of ice cream with the additionÂ white rice and white glutinous rice bran. The addition of different types of rice and glutinous rice bran decrease level of acceptance includes the color, flavor, texture, and flavor of ice cream. Conclusions: The highest fiber content is in the ice cream with the addition of black glutinous rice bran. The lowest fat content is in the ice cream with the addition of white rice bran. Recommended ice cream is ice cream with the addition of white glutinous rice bran.